Identifying risks in dementia care: Insights from a qualitative study with clinical pharmacists - Alice Burnand; Kumud Kantilal; Abi Woodward; Cini Bhanu; Jill Manthorpe; Mine Orlu; Greta Rait; Kritika Samsi; Liz Sampson; Victoria Vickerstaff; Jane Wilcock; Yogini Jani; et al. (PLoS ONE, 2025)
Introduction People with dementia experience complex healthcare needs. Clinical pharmacists play a crucial role in optimising medication management and ensuring patient safety within the primary care setting. However, little is known about the specific barriers and challenges they face when delivering dementia care. This study investigates the safety of dementia care in the community, focusing on the experiences of clinical pharmacists. Methods A qualitative study using semi-structured interviews with clinical pharmacists. Data analysis employed codebook thematic analysis, guided by the SEIPS 2.0 framework. Results Thirteen clinical pharmacists were interviewed. Key risks include variations in pharmacist expertise, communication barriers, limited resources, and systemic challenges. Using the SEIPS 2.0 framework, the complex interactions between work systems (people, tools, tasks, organisation and environment) and work processes were identified, which impact safety outcomes for both clinical pharmacists and people with dementia. Conclusions Interviews revealed a spectrum of risks associated with dementia care in primary care. This study highlights the complex interplay of factors influencing the safety of dementia care. A proactive, multifaceted approach addressing training, interprofessional collaboration, and system-level adaptations is crucial to mitigate these risks and enhance patient safety in dementia care.